An investigation of the nature of RUSKIN BOND's writings - Kumar, Mani; Babu, Suresh (The journal of contemporary issues in business and government, 2017)
This research project has been done in order to investigate and evaluate the style of Ruskin Bond's short tales about nature. Any appraisal of Ruskin Bond as a nature lover must to take into consideration the genre of his short storey writing, which has developed the fragrance of nature in its many forms. The Himalayan Mountains are in this region. Bond's imagery and sensuality are not overpowered by the other characters. any portrayal of nature that is metaphorical in character. They develop as a consequence of his affection for and concern for them. a dedication to the environment He does not suffocate the spontaneity of natural images by using a camera. associated with a second layer of significance or as a demonstration of his understanding Stunningly beautiful and He is stirred by the spectacular vibrations of nature, which he enjoys sharing with his readers. Nature, the Himalayan region, exploration, and imagination are some of the key phrases.